Implications of the COVID-19 Pandemic for Tax Systems - Case of Poland - Leszek BOROWIEC; Waldemar SZYMAŃSKI (Communications of International Proceedings, 2021)
The aim of the anti-crisis solutions, also referred to as packages or “shields” is to ensure the stability of the financial sector while guaranteeing security for businesses and workers. These functions are to be fulfilled by anti-crisis instruments, such as additional taxation of the financial sector or tax preferences. The epidemiological crisis and its associated economic and social impacts have brought fiscal policy into the attention of politicians and economists. The aim of the study is to evaluate the tax solutions introduced in relation to the ongoing COVID–19 pandemic, in the context of effectiveness for the stability of economic entities and maintenance of employment. A necessary condition for the effectiveness of anti-crisis fiscal policies is the recognition of the nature of a crisis, in this case: creating downtime and restrictions for enterprises, payment gridlock or loss of employment.
Keywords: COVID -19; Taxes; Tax System; Tax Functions; Tax Base; Tax Efficiency; Economic Crisis.